Menciptakan Lingkungan Digital yang Islami dan Beretika: Strategi Pengembangan Teknologi Informasi Berbasis Nilai-Nilai Islam dalam Era Modern - Kayla Salva Alishiha Zahra; Hilma Najiyyah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
The exponential growth of digital technology has profoundly reshaped the communicative landscape of Muslim communities across the globe, fundamentally altering how they access information, forge religious identities, and engage in collective discourse. This study examines the imperative of building an Islamic and ethical digital ecosystem grounded in three foundational pillars of Islamic thought: theological monotheism (tawhid), Islamic jurisprudence (fiqh), and moral excellence (akhlakul karimah). Employing a qualitative methodology through systematic literature review and critical discourse analysis, this research synthesizes perspectives drawn from Islamic studies, digital ethics, communication theory, and social informatics. The findings demonstrate that Islamic moral principles encompassing truthfulness (sidq), integrity (amanah), wisdom (hikmah), and justice (adl) constitute a robust and coherent normative framework for governing conduct in digital spaces. The study maps four interconnected dimensions of an Islamic digital ecosystem: theological grounding for online behavior, ethical interaction in social media environments, creative dakwah through positive content generation, and collective approaches to countering moral hazards including misinformation, cyberbullying, and digital addiction. The research concludes that without deliberate, coordinated engagement from religious scholars, educators, content creators, and policymakers, digital spaces risk amplifying moral degradation rather than fostering spiritual development. The paper proposes a multi-stakeholder model for constructing an Islamic digital culture that is genuinely value-driven, participatory, and adaptive to the evolving technological landscape rather than merely rule-compliant.